PENGARUH PERTUMBUHAN PERUSAHAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Elya Rasita; Zaria Desma; Selvita Oktryani (Universitas Muhammadiyah Bengkulu, 2025)
The purpose of this research is to examine the influence of company growth and dividend policy on the value of companies in the food and beverage manufacturing sector for the period 2020-2023. This research involves 226 manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2023. The sample in this study consists of 13 companies. The sampling technique used in this research is purposive sampling. The data collection technique used in this research is secondary data sourced from annual reports and financial reporting from www.idx.co.id and official company websites. This data analysis technique uses multiple linear regression processed with SPSS 26. This test consists of descriptive statistics, classical assumption tests, and hypothesis tests. Keywords: Company Growth, Dividend Policy, Company Value